Immigration, Literacy, and Adult Education: The Policy Context - Lurong Wang (Adult Education Research Conference, 2007)
This paper examines the institutional assumption of literacy that underpins Canadian immigration policy and adult literacy policy. My analysis focuses on how adult immigrants are positioned in policy contexts and what gaps or contradictions exist between the reality and policy discourses.